RELATIONSHIP BETWEEN PARENTING STYLES AND ACADEMIC PERFORMANCE IN PAKISTANI STUDENTS: A LITERATURE REVIEW - Abrar, Tahira; Zeshan, Muhammad; Iqbal, Waheed (Journal of Pakistan Psychiatric Society, 2023)
There is ample research on the role of parenting in the academic performance of students that highlights parenting styles and their importance. While this research is extensively done in the Western world, research in the cultural context of South Asia and particularly Pakistan is lacking. Therefore, this review was done to analyse the existing research on the two variables in Pakistan and to provide guidance for future research. The review included studies that were previously conducted on parenting styles and academic performance of students from elementary to postgraduate level. The focus was to analyse relevant data exclusively from Pakistan. For this purpose, 17 studies from the past ten years were selected. Articles from six databases (including PubMed, Google Scholar, Springer Link, Science Direct, SAGE Journals, and Taylor and Francis Journals) were identified relating to the topic using a pre-established set of terms that included both parenting styles and academic performance. 15 of the studies highlighted that parenting styles affect the academic achievement of students, while 2 studies showed no association. It was analysed that the authoritative parenting style was the most effective in enhancing the academic performance of young children. More in-depth research is needed on parenting styles to have a better understanding of the cultural effect of parenting styles on academic performance in Pakistan.